Bluetooth Mobile Advertising System Using Pull-Based Approach - Halim, AH; Fauzi, AH; Tarmizi, S (IEEE, 2024)
The focus of this paper is on the implementation of Bluetooth as a tool to provide m-advertising (mobile advertising). The paper attempts to introduce the implementation of Bluelooth m-advertising system based on user-driven concept using pull-based approach. User-driven concept gives flexibility to end users to select the preferred advertisements from the server while pull-based m-advertising provides advertisement to users based on their willingness and request. This paper also will address two issues in push-based m-advertising systems, which are spamming and time limit.